Migration Route Reconstruction of Different Cohorts of Ommastrephes bartramii in the North Pacific Based on Statolith Microchemistry - Han, Peiwu; Fang, Zhou; Li, Nan; Chen, Xinjun (Frontiers in Marine Science, 2022)
Ommastrephes bartramii is one of the important commercial fishery species in the North Pacific Ocean. It always migrates for a long distance in order to spawning and feeding. Understanding its migration route can be the basis for the sustainable development of the fisheries and scientific management of this species. Cephalopod statoliths contain a wealth of ecological information, which can provide useful information for studying spatio-temporal distribution. In this study, the statolith elements of winter-spring and autumn cohorts of O. bartramii in the North Pacific Ocean were measured by Laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS). The differences in both composition and concentrations of elements between winter-spring and autumn cohorts were analyzed and the migration route were reconstructed. The analysis showed that the highest concentrations of elements in different cohorts was calcium (Ca). The concentrations of Ca, strontium (Sr), sodium (Na), iron (Fe), barium (Ba), and lithium (Li) showed significant differences between two cohorts (P < 0.01). Mg, Ba, Sr and Na were selected as the key elements in the two cohorts based on random forest method. Five clusters were obtained through chronological clustering, representing the five ontogenetic stages. Different cohorts selected different elements to fit the regression model with the corresponding water temperature. The high probability of occurrence in a particular area represented the possible optimal squid location based on a Bayesian model, and the potential migration routes of the different cohorts were reconstructed. This study shows that statoliths microchemistry can provide useful information for identifying the distribution and migration of oceanic squid.